Disaster communication of the Merapi slope community - Ulfah Hidayati; Pratiwi Wahyu Widiarti; Eko Prasetyo Nugroho Saputro (Universitas Negeri Yogyakarta, 2021)
This research aims to examine disaster communication performed by the community of Turgo, Purwobinangun, Pakem. Sleman. The research was conducted utilizing a qualitative method, and the data were collected through interviews and Focus Group Discussions. The research objects include the community members living in Turgo consisting of teenagers, adults, the elderly, the search and rescue (SAR) team, and village heads. The research results show that the people living in Turgo utilize many sources of information in accessing disaster information, including surveillance and reconnaissance posts (wastai posts), social media, interpersonal communication, and group communication. The information is delivered through Whatsapp Group, Youtube, Twitter, Instagram, direct/ face-to-face communication, traditional bamboo slit drum (kentongan), motorcycle horns, and speakers. In addition, the resident's response is very positive in responding to any call/order from the authorities. In other words, no citizen rejected the call given. Also, opinion leaders do not have a significant role in disaster communication. The SAR team has a higher position than the opinion leader as they know the conditions in the field better